Hemotorax jako komplikace torakotomie - Cermák, J; Fiala, P; Novák, K; Hytych, V; Moucková, M (Rozhledy v chirurgii, 1991)
In 1969 to 1989 in the Research Institute of Tuberculosis and Respiratory Diseases in Prague a total of 3583 thoracotomies were performed. Of these during the postoperative period 29 patients were re-operated on account of continuing haemorrhage into the pleural cavity. This is approximately 0.8% of all thoracotomies. Sixteen patients had to be re-operated within 12 hours after operation, 12 patients were re-operated later than 12 hours after operation but within 24 hours, one patient was re-operated later than 24 hours after operation. The cause of haemothorax was in the first place capillary haemorrhage from a lacerated pleura, in the second place haemorrhage from a severe intercostal artery at the very site of the thoracotomy. Other causes of haemorrhage such as haemorrhage from the bronchial artery and its branches are not frequent. None of the patients had to be re-operated on account of haemorrhage from the major arteries of the pulmonary hilus. Administration of small doses of heparin before and after operation did not influence the number of re-operations on account of haemothorax.
Keywords: Hemothorax; hemotorax; Humans; Thoracotomy; lidé; torakotomie